HEMATOLOGICAL CHARACTERISTIC OF THE FEMALE ASIAN VINE SNAKE (AHAETULLA PRASINA BOIE, 1827) - I Gusti A. Ayu Ratna Puspita Sari; Endah Sri Palupi (UPT Penerbitan Universitas Jember, 2016)
There is less information about the hematological characteristic of snake in Indonesia. Morphology and morphotic elements size of erythrocyte and leukocyte of the female Asian Vine Snake (Ahaetulla prasina) in North Purwokerto, Indonesia, were studied. Blood was sampled by cardiac puncture and blood cells morphology and size were observed and measured from prepared blood smears. Erythrocyte was nucleated and oval in shape. Leukocyte were lymphocytes, heterophils, eosinophils, basophils and monocytes. The erythrocyte was slightly differ from those of other squamates. Morphology and morphotic size of blood cells provided information about the physiological character of Asian Snake Vine. More comprehensive study is necessary to understand the correlation of blood cells characteristic of snakes with other characteristic.